Factors associated with the use of benzodiazepines in primary care patients (Research, Society and Development, 2023)
Objective: To analyze the factors associated with the use of benzodiazepines in primary care patients. Methods: This is descriptive research, with cross-sectional quantitative field analysis. The research took place in the city of Guanambi, BA and the research participants were patients who stretch in the Basic Health Units of the city. The sample consisted of 62 randomly selected participants from both genders. To carry out the data collection, a questionnaire with direct and objective questions was used. The procedure used followed and took in consideration the international standards of experimentation with humans, having been approved by the Ethics Committee. Results: It was evidenced that most participants (74.2%) are women, with a prevalence in the age group of 31-40 years, with clonazepam being the most used drug class (53.2%) and anxiety being the most common cited complaint (53.2%). Conclusion: Most of the participants trust the treatment performed with benzodiazepines and fully adhere to the recommended treatment.